Building Brand Loyalty through Digital Media in the FMCG Segment - Vondráčková, Petra; Karlíček, Miroslav, 1979-; Pěničková, Vlasta; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
Diploma thesis studies the topic of brand loyalty within the digital media and is specifically targeted on FMCG segment. Brand loyalty is defined as a commitment to re-buy a specific product or service in the future, no matter of any external influences. In case of FMCG, there are several influencers of brand loyalty that must be taken care of, e.g. core offering, demographics, elasticity level or share of wallet. The objective of this thesis is to define a digital strategy for a dairy product brand, which aims at increasing its brand loyalty. In order to achieve that, the author has reviewed academic literature on the topic of brand loyalty, as well as on digital media and their influence on loyalty. The digital strategy, defined in the final part of the thesis, is based on the author's research dealing with brand's online performance, analysis of competitive digital activities, analysis of related online content and analysis of Czech digital environment.
Vedoucí práce: Miroslav Karlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses